THE RELATIONS OF THE UNITED STATES WITH THE COUNTRIES OF LATIN AMERICA AND THE PECULIARITY OF LATIN AMERICA (Academia Science Repository, 2023)
In this article, the relationship of the United States with the countries of Latin America and the characteristic of Latin America. The role of Latin American countries in the world community is described.